Peran Afghanaid dalam Pengentasan Kemiskinan di Afghanistan Tahun 2015-2020 - Anriyani, Reski; Mamma, Beche Bt. (Universitas Bosowa, 2025)
Afghanaid is an international organization working in the humanitarian sector to overcome poverty in Afghanistan for more than 40 years. This research aims to find out and explain the role of Afghanaid in helping to eradicate poverty in Afghanistan based on 2015-2020. The research method used in this research is descriptive-qualitative, based on previous research, books, journals and libraries, which carry out similar research by collecting data through several sources in the form of documents. Most of the data used in this research was obtained through the official Afghanaid website and several research journals that discuss poverty in Afghanistan. The results of this research show that the success of the Afghanaid program is highly dependent on long-term funding and resources needed to achieve the poverty alleviation target. As a forum, Afghanaid has created collaboration with local and international parties. Still, unfortunately, Afghanaid has not succeeded in producing specific policies through this collaboration that can be used as guidance by its members. Resources are also the main obstacle to success, which is used as poverty alleviation based on cooperation and only focuses on internal policies.